(untitled) (Journal of actual problems of jurisprudence, 2019)
In the Republic of Kazakhstan sources of land law is the Constitution of the Republic of Kazakhstan, the Land Code of the Republic of Kazakhstan and other regulatory legal acts. Adopted in July 20, 2003 Land Code of the Republic of Kazakhstan – introduced private ownership of agricultural land. Land reform is the linchpin of economic transformation, and its direction is determined relationship to the land. And at the present stage of development of land relations pravovvyh require regulation of such issues as promoting improved quality of land, penalties for environmental damage from fines to termination of the land use rights, the introduction of compensatory payments, compensation for damages and losses in the seizure of land, the formation of the land market, strengthening responsibility for the violation of land legislation. Land reform is a combination of legal, economic, organizational and technical measures ensuring a qualitatively new structure of land ownership and land use in the period since the republic’s economy into the market economy. Keywords: land relations, private property, public property, the bill, land laws.